Traditional musical culture of kazakhstan at the turn of the centuries - Tatkenova, Sholpan; Sara Kuzembay, Aklima Omarova, Ainur Kaztuganova, (Opción, 2019)
This article examines the song tradition of the northern region of Central Kazakhstan at the turn of 20th century. In the course of this study songs of Nurzhan Naushabayev were closely observed, were identified their stylistic features and rhythmic patterns. As a result, being an example for the younger generation, the above-mentioned composers motivated many performers and creative personalities to actively develop their musical material. In conclusion, the influence of written culture and Eastern poetry played a major role in the formation of artistic taste of Nurzhan and became a style distinctive feature that can be traced in his works.